The Definition and Social Danger of the Crime of Robbery through Employment or Distribution - Marufaliyev is the son of Ahrorbek Avazbek, (European Journal of Life Safety and Stability (2660-9630), 2024)
This article analyzes the concept of the crime of embezzlement, its social danger, and the history of its development. The article also discusses the scientific debate with the views of national and foreign scientists. The legislation of foreign countries on the crime of embezzlement or expropriation was studied, and proposals and recommendations for national legislation were developed.